Borderland historiography in Pakistan. Issue 4 (1st October 2016) - Caron, James
ABSTRACT: In this article, I survey historical writing related to the twentieth-century Afghan–Pakistan frontier, particularly Pashtun-majority locations in Khyber-Pakhtunkhwa: the former Northwest Frontier Province. I focus on works that help conceptualize history beyond issues of political economy. Some locate themselves solely in the Anglophone academy, but this is not intended as a complete survey of their field. Rather, I place those works in dialogue with, and prioritize, eclectic histories that are both 'about' and 'of' the borderland; and I discuss this combined field with reference to other scholarly work on 'thinking from borders' in both the political–economic and intellectual–cultural senses. My goal is to intervene in the second set of borders, to disrupt boundaries between global academic culture and 'other' intellectual milieus. Taking tazkiras and autobiographies as examples, I argue that genres of writing from regions heavily fragmented by imperial bordering, among other factors, are social theory in action, not just representation for historians to appropriate. Engaging border history genres and taking seriously the insight they offer requires a willingness to engage the webs of social commitments that produced these works: to work in contribution to their milieus rather than merely writing about them.